2018
DOI: 10.1007/s00268-018-4629-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient Frailty Should Be Used to Individualize Treatment Decisions in Primary Hyperparathyroidism

Abstract: Patient frailty is associated with increased complications, reoperation and prolonged LOS in patients undergoing parathyroidectomy for PHPT. The risks of surgical management should be weighed against potential benefits in frail patients with PHPT to individualize treatment decisions in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…Cases with multiple tumours are particularly more complicated, as a fall in the intraoperative PTH to the lower end of a normal range cannot guarantee that all tumours have been removed [19][20][21]. A reduction in intraoperative PTH by more than 50% after the procedure is a predictive factor [22,23] and may be prevented by preoperative supplementation with bisphosphonates [24,25]. Age is not a relevant contributing factor for the occurrence of complications [26,27], while anesthesia can often cause sudden elevation of PTH levels in patients suffering from hyperparathyroidism [28,29] and can worsen renal functions [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Cases with multiple tumours are particularly more complicated, as a fall in the intraoperative PTH to the lower end of a normal range cannot guarantee that all tumours have been removed [19][20][21]. A reduction in intraoperative PTH by more than 50% after the procedure is a predictive factor [22,23] and may be prevented by preoperative supplementation with bisphosphonates [24,25]. Age is not a relevant contributing factor for the occurrence of complications [26,27], while anesthesia can often cause sudden elevation of PTH levels in patients suffering from hyperparathyroidism [28,29] and can worsen renal functions [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Women account for the majority of patients with PHPT, with a female to male ratio as high as 3 or 4: 1. 20 In this study, bone pain was present in 83% of patients, 50% of patients presented fractures, and 37% had fatigue and were uncomfortable. Because of the long course of the disease, 13% of patients had severe bone damage and skeletal deformities.…”
Section: Discussionmentioning
confidence: 53%
“…However, they did not consider well-known complications such as laryngeal nerve injury and hypocalcemia, thus limiting comparability ( 22 ). In 2018, another study reported a higher risk of complications in frail and oldest patients >75 years ( 24 ). But again, as they also investigated non-surgical complications, comparability might be hindered.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported conflicting findings concerning PTX-safety in elderly patients ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ).…”
Section: Introductionmentioning
confidence: 97%